Paul Ludwig Landsberg, a Knight Errant of the Spirit in Barcelona - Escribano, Xavier (Journal of Catalan Intellectual History, 2015)
Paul Ludwig Landsberg (Bonn, 1901-Oranienburg, 1944) was a prominent student of the German philosopher Max Scheler. Born into a Jewish family, Landsberg was a professor at the University of Bonn until 1933, when he left his country at the time of Hitler’s rise to power. In spring 1934, Joaquim Xirau, dean of the Faculty of Philosophy and Letters of the University of Barcelona, invited him to give lectures and teach classes in the Seminar on Education. During the academic years 1934-35 and 1935-36, Landsberg led classes in Barcelona on St. Augustine, Maine de Biran, Nietzsche and Scheler. His personality and his teaching were to leave a lasting impression in the memory of an entire generation of young university students who joined in the intellectual climate fostered by university autonomy and by Joaquim Xirau’s encouragement. Drawing closely on Phenomenology, Existentialism and Personalism, Landsberg was especially known for his reflections on the experience of death and the moral problem of suicide. His own tragic end in the Sachsenhausen concentration camp, where he died of starvation and exhaustion, further underscores the unity of thought and life that typified his work. keywords: Paul Ludwig Landsberg, University of Barcelona, experience, death, Nietzsche, Max Scheler.